Contact ion-pair SN2 reactions activated by Lewis Base Phase transfer catalysts - Ju Gyeong Jeong; Young-Ho Oh; Tae Hyun Park; Sung-Sik Lee; Dong Wook Kim; Sungyul Lee (Nature Communications)
Abstract We present experimental probes of contact ion-pair (CIP) SN2 reactions for simplest prototype systems by 19F-NMR spectroscopy. This study provides crucial evidences for the reactions of CIP metal salts facilitated by Lewis base phase transfer catalysts (PTCs) [2,2,2]-cryptand, 18-crown-6, pentaethylene glycols (pentaEGs) and BINOL–based pentaEG. The 19F-NMR spectra of MF (M = K, Cs) ion-pairs in various solvents are used as fingerprinting tools to identify the CIP CsF/PTC/substrate complexes in SN2 reactions. Examination of the prototype reactions demonstrates that the novel CIP mechanism, which is in sharp contrast to the conventional perspectives, may account for the observed phenomenal efficiency of the SN2 processes using the alkali metal salts under the influence of various PTCs. In this extremely efficient and selective protocol of wide applicability, the CIP MF is activated by the Lewis base PTCs acting on the counter-cation M+ to drastically mitigate the latter’s retarding Coulomb forces on the adjacent nucleophile F-, with or without the participation of hydrogen bonds.